Anti-Muellerian hormone levels in plasma of Holstein-Friesian heifers as a predictive parameter for ovum pick-up and embryo production outcomes - VERNUNFT, Andreas; SCHWERHOFF, Mona; VIERGUTZ, Torsten; DIEDERICH, Mike; KUWER, Andreas (Journal of Reproduction and Development, 2015)
The aim of this study was to investigate whether plasma anti-Muellerian hormone (AMH) levels of Holstein-Friesian heifers could be used to predict ovum pick-up (OPU) and embryo production outcomes. Plasma samples and data were collected from 64 heifers, which underwent repeated OPU with subsequent in vitro embryo production followed by embryo flushing after superovulation. AMH levels were significantly positively correlated with the number of follicles aspirated per OPU session (r = 0.45), recovered oocytes per OPU (r =0.43) and in vitro produced embryos per OPU (r = 0.28). No significant correlations between AMH and in vivo produced embryos were ascertained. Our results suggest that correlations between AMH and outcomes of an OPU-IVF program are too low to use AMH as a precise predictive parameter for the success of a particular OPU procedure in Holstein-Friesian heifers. However, AMH can help to identify groups of very good or very poor oocyte donors.